PENCITRAAN POLITIK KANDIDAT PADA PEMILIHAN BUPATI DI KABUPATEN WAY KANAN 2020 - Adie Nurjana Resma (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Baturaja, 2023)
This study aims to see the process of candidate Juprius – Rina Marlina and Adipati Surya – Ali Rahman in the 2020 regional head elections in Way Kanan Regency, especially in terms of political imagery and political strategy using Dan Nimo's theory by looking at pure publicity political imagery, Free Ride Publicity, Tie-in Publicity, Paid Publicity. The method used is a qualitative descriptive research method through interviews with speakers, namely successful teams, religious and community organization leaders, academics, youth leaders and MSME actors. Secondary data consists of books and related documentation. The results showed that the couple 01 Juprius – Rina Marlina tried to build imaging through Free Ride Publicity, Paid Paid Publicity and Pure Publicity. This was done by the pair of candidates 01 to raise their image in the eyes of the public to get a victory. While the candidate pair 02 Raden Adipati Surya-Ali Rahman used Pure publicity, Free Ride Publicity, Tie-in Publicity, Paid Publicity. Which then won back Raden Adipati Surya for the second priode. The strategies carried out, both utilize mass organizations, groups, community groups and assemblies.In this usefulness that is more effective for mobilizing it is the successful team of the pair of candidates 02. From the conclusions of this study, the political imagery of the couple and the strategy of 01 have not been able to succumb to the petaha which is still strong in maintaining the image and gaining the sympathy of the people. On the other hand, the pair of candidates 02 are able to create and build their image through the strategies made. Looking at the theory used by the examiner of the difference between the two pairs of candidates, it is the pair of candidat 01 is not all used. While the 02 couple is able to take advantage of existing and owned resources through office and power.